Learning status description for personalised C language e-learning environment. (2017) - Yan, Yu; Hara, Kohei; Kazuma, Takenobu; He, Aiguo
It is important for personalised e-learning environment to have computational learning status information of individual learners. This article proposes a method to describe syntax-knowledge-point (SKP for short)-based learning status of individual learners for personalised C programming e-learning environment. This method utilises syntactic knowledge information extracted from C program source code. Firstly, it gathers all offered SKP from example source codes and exercises' model answers in teaching materials; Then, for each learner, it collects his SKP-based learning activities by extracting SKP information from the source code the learner has read or been taught or submitted; Finally, for each learner, his understanding of every SKP can be estimated from the collected data. And individual learners learning status is described by the set of his understanding of each SKP. Experiments show that the proposed method is effective and feasible to get individual learners learning status in detail level by the computer system.